1977
DOI: 10.1111/j.1365-2338.1977.tb02407.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Canker and Dieback Disease of Apricots (Pseudomonas syringae van Hall)

Abstract: Bacterial canker and dieback (Pseudomonas syringae van Hall) of apricot is a widespread disease in Europe, except for the Mediterranean areas. Cankers usually develop at pruning wounds or other points of injury. Phloem and cambium become susceptible from just after leaf drop until budding. If the phloem necrosis does not girdle the branch or trunk, cankers develop by the middle or the end of summer. In early summer, the bacterium actually dies out in the infected tissue, and the tree remains resistant during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1977
1977
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…Bacterial cancer symptoms on stone fruits (especially apricot) are usually confused with symptoms of frost damage and Cytospora canker (Leucostoma canker or Valsa Canker) caused by Cytospora spp. (Baker, 2022;Fitzgerald et al, 2001;Gauthier et al, 2022;Klement, 1977;Lawrence et al, 2018). Sequencing data for four genes of these pathovars were downloaded from more than one strain in NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial cancer symptoms on stone fruits (especially apricot) are usually confused with symptoms of frost damage and Cytospora canker (Leucostoma canker or Valsa Canker) caused by Cytospora spp. (Baker, 2022;Fitzgerald et al, 2001;Gauthier et al, 2022;Klement, 1977;Lawrence et al, 2018). Sequencing data for four genes of these pathovars were downloaded from more than one strain in NCBI.…”
Section: Discussionmentioning
confidence: 99%
“…Smatramo da je infekcija nastala usled visoke vlažnosti i nižih temperatura. Ova bakterija poseduje svojstvo da se pri nižim temperaturama uspešnije razvija i širi, nego pri uobičajenim vremenskim uslovima za ovo doba godine (Klement, 1977;Spots and Cervantes, 1996;Arsenijević, 1997). Izvor inokuluma može biti epifitna populacija bakterije koja se razvija na listovima i cvetovima voćaka bez ispoljavanja simptoma bolesti (Lattore and Jones, 1979).…”
Section: Rezimeunclassified
“…Although there have been several reports that pruning cuts provide infection sites for bacterial pathogens (Wormald 1931;Dowler & Petersen 1966;Vigouroux 1970;Luisetti et al 1976;Klement 1977), I have rarely confirmed these wounds as infection sites for bacterial disease development. Heavy pruning may create sites for infection but may also affect a tree's physiology, rendering it more susceptible.…”
Section: Pruningmentioning
confidence: 99%